Changes of intestinal microbiota in early life. (18th March 2020) - Ficara, Monica; Pietrella, Elisa; Spada, Caterina; Della Casa Muttini, Elisa; Lucaccioni, Laura; Iughetti, Lorenzo; Berardi, Alberto
Abstract: There is an increasing evidence that the intestinal microbiota plays a pivotal role in the maturation of the immune system and in the prevention of diseases occurring during the neonatal period, childhood, and adulthood. A number of nonphysiological conditions during the perinatal period (i.e. caesarean section, prolonged hospitalization, formula feeding, low gestational age) may negatively affect the normal development of the microbiota, leading to decreased amounts of lactobacilli and bifidobacteria and increased amounts of Clostridia. In addition, perinatal antibiotics can cause intestinal dysbiosis that has been associated with short- and long-term diseases. For example, prolonged early empiric antibiotics increase the risk of necrotizing enterocolitis (NEC) and late-onset sepsis (LOS) in preterm neonates, whereas the administration of intrapartum antibiotic prophylaxis (IAP) has been associated with inflammatory bowel diseases, obesity, and atopic conditions, such as eczema and wheezing. Promoting breastfeeding, reducing the length of hospital stay, and reducing unnecessary antibiotic therapies are useful strategies to counterbalance unintended effects of these conditions.